Sublattice asymmetry of impurity doping in graphene: A review - Lawlor, James A.; Ferreira, Mauro S. (Beilstein Journal of Nanotechnology, 2014)
In this review we highlight recent theoretical and experimental work on sublattice asymmetric doping of impurities in graphene, with a focus on substitutional nitrogen dopants. It is well known that one current limitation of graphene in regards to its use in electronics is that in its ordinary state it exhibits no band gap. By doping one of its two sublattices preferentially it is possible to not only open such a gap, which can furthermore be tuned through control of the dopant concentration, but in theory produce quasi-ballistic transport of electrons in the undoped sublattice, both important qualities for any graphene device to be used competetively in future technology. We outline current experimental techniques for synthesis of such graphene monolayers and detail theoretical efforts to explain the mechanisms responsible for the effect, before suggesting future research directions in this nascent field.
Keywords: band gap; electronic transport; graphene; nitrogen doping; sublattice asymmetry

(untitled) - Geim, A. K.; Novoselov, K. S. (Nat. Mater., 2007)

(untitled) - Novoselov, K. S.; Fal’ko, V. I.; Colombo, L.; Gellert, P. R.; Schwab, M. G.; Kim, K. (Nature, 2012)

(untitled) - Chen, J.-H.; Jang, C.; Xiao, S.; Ishigami, M.; Fuhrer, M. S. (Nat. Nanotechnol., 2008)

(untitled) - Allen, M. J.; Tung, V. C.; Kaner, R. B. (Chem. Rev., 2010)

(untitled) - Schwierz, F. (Nat. Nanotechnol., 2010)

(untitled) - Lin, Y.-M.; Jenkins, K. A.; Valdes-Garcia, A.; Small, J. P.; Farmer, D. B.; Avouris, P. (Nano Lett., 2009)

(untitled) - Zhang, Y.; Tang, T.-T.; Girit, C.; Hao, Z.; Martin, M. C.; Zettl, A.; Crommie, M. F.; Shen, Y. R.; Wang, F. (Nature, 2009)

(untitled) - Li, X.; Wang, X.; Zhang, L.; Lee, S.; Dai, H. (Science, 2008)

(untitled) - Naumov, I. I.; Bratkovsky, A. M. (Phys. Rev. B, 2011)

(untitled) - Novoselov, K. (Nat. Mater., 2007)

(untitled) - Zhou, S. Y.; Gweon, G.-H.; Fedorov, A. V.; First, P. N.; de Heer, W. A.; Lee, D.-H.; Guinea, F.; Castro Neto, A. H.; Lanzara, A. (Nat. Mater., 2007)

(untitled) - Chang, C.-K.; Kataria, S.; Kuo, C.-C.; Ganguly, A.; Wang, B.-Y.; Hwang, J.-Y.; Huang, K.-J.; Yang, W.-H.; Wang, S.-B.; Chuang, C.-H.; Chen, M.; Huang, C.-I.; et al. (ACS Nano, 2013)

(untitled) - Avouris, P. (Nano Lett., 2010)

(untitled) - Kim, K.; Choi, J.-Y.; Kim, T.; Cho, S.-H.; Chung, H.-J. (Nature, 2011)

(untitled) - Islam, M. S.; Ushida, K.; Tanaka, S.; Makino, T.; Hashimoto, A. (Comput. Mater. Sci., 2014)

(untitled) - Casolo, S.; Martinazzo, R.; Tantardini, G. F. (J. Phys. Chem. C, 2011)

(untitled) - Lherbier, A.; Blase, X.; Niquet, Y.-M.; Triozon, F.; Roche, S. (Phys. Rev. Lett., 2008)

(untitled) - Martinazzo, R.; Casolo, S.; Tantardini, G. F. (Phys. Rev. B, 2010)

(untitled) - Palacios, J. J.; Fernández-Rossier, J.; Brey, L. (Phys. Rev. B, 2008)

(untitled) - Cresti, A.; Ortmann, F.; Louvet, T.; Van Tuan, D.; Roche, S. (Phys. Rev. Lett., 2013)

(untitled) - Pereira, V. M.; Lopes dos Santos, J. M. B.; Castro Neto, A. H. (Phys. Rev. B, 2008)

(untitled) - Wei, D.; Liu, Y.; Wang, Y.; Zhang, H.; Huang, L.; Yu, G. (Nano Lett., 2009)

(untitled) - Guan, L.; Cui, L.; Lin, K.; Wang, Y. Y.; Wang, X. T.; Jin, F. M.; He, F.; Chen, X. P.; Cui, S. (Appl. Phys. A, 2011)

(untitled) - Zhang, C.; Fu, L.; Liu, N.; Liu, M.; Wang, Y.; Liu, Z. (Adv. Mater., 2011)

(untitled) - Telychko, M.; Mutombo, P.; Ondráček, M.; Hapala, P.; Bocquet, F. C.; Kolorenč, J.; Vondráček, M.; Jelínek, P.; Švec, M. (ACS Nano, 2014)

(untitled) - Bangert, U.; Pierce, W.; Kepaptsoglou, D. M.; Ramasse, Q.; Zan, R.; Gass, M. H.; Van den Berg, J. A.; Boothroyd, C. B.; Amani, J.; Hofsäss, H. (Nano Lett., 2013)

(untitled) - Lin, Y.-C.; Lin, C.-Y.; Chiu, P.-W. (Appl. Phys. Lett., 2010)

(untitled) - Wang, Y.; Shao, Y.; Matson, D. W.; Li, J.; Lin, Y. (ACS Nano, 2010)

(untitled) - Joucken, F.; Tison, Y.; Lagoute, J.; Dumont, J.; Cabosart, D.; Zheng, B.; Repain, V.; Chacon, C.; Girard, Y.; Botello-Mendez, A. R.; Rousset, S.; Sporken, R.; et al. (Phys. Rev. B, 2012)

(untitled) - Wang, H.; Maiyalagan, T.; Wang, X. (ACS Catal., 2012)

(untitled) - Wang, H.; Xie, M.; Thia, L.; Fisher, A.; Wang, X. (J. Phys. Chem. Lett., 2014)

(untitled) - Gao, H.; Song, L.; Guo, W.; Huang, L.; Yang, D.; Wang, F.; Zuo, Y.; Fan, X.; Liu, Z.; Gao, W.; Vajtai, R.; Hackenberg, K.; et al. (Carbon, 2012)

(untitled) - Usachov, D.; Vilkov, O.; Grüneis, A.; Haberer, D.; Fedorov, A.; Adamchuk, V. K.; Preobrajenski, A. B.; Dudin, P.; Barinov, A.; Oehzelt, M.; Laubschat, C.; Vyalikh, D. V. (Nano Lett., 2011)

(untitled) - Tang, Y.-B.; Yin, L.-C.; Yang, Y.; Bo, X.-H.; Cao, Y.-L.; Wang, H.-E.; Zhang, W.-J.; Bello, I.; Lee, S.-T.; Cheng, H.-M.; Lee, C.-S. (ACS Nano, 2012)

(untitled) - Fan, X.; Shen, Z.; Liu, A.; Kuo, J.-L. (Nanoscale, 2012)

(untitled) - Lherbier, A.; Botello-Méndez, A. R.; Charlier, J.-C. (Nano Lett., 2013)

(untitled) - Botello-Méndez, A. R.; Lherbier, A.; Charlier, J. C. (Solid State Commun., 2013)

(untitled) - Zhao, L.; He, R.; Rim, K. T.; Schiros, T.; Kim, K. S.; Zhou, H.; Gutiérrez, C.; Chockalingam, S. P.; Arguello, C. J.; Pálová, L.; Nordlund, D.; Hybertsen, M. S.; et al. (Science, 2011)

(untitled) - Lv, R.; Li, Q.; Botello-Méndez, A. R.; Hayashi, T.; Wang, B.; Berkdemir, A.; Hao, Q.; Elias, A. L.; Cruz-Silva, R.; Gutiérrez, H. R.; Kim, Y. A.; Muramatsu, H.; et al. (Sci. Rep., 2012)

(untitled) - Zhao, L.; Levendorf, M.; Goncher, S.; Schiros, T.; Pálová, L.; Zabet-Khosousi, A.; Rim, K. T.; Gutiérrez, C.; Nordlund, D.; Jaye, C.; Hybertsen, M.; Reichman, D.; et al. (Nano Lett., 2013)

(untitled) - Zabet-Khosousi, A.; Zhao, L.; Pálová, L.; Hybertsen, M. S.; Reichman, D. R.; Pasupathy, A. N.; Flynn, G. W. (J. Am. Chem. Soc., 2014)

(untitled) - Deretzis, I.; La Magna, A. (Phys. Rev. B, 2014)

(untitled) - Lawlor, J. A.; Gorman, P. D.; Power, S. R.; Bezerra, C. G.; Ferreira, M. S. (Carbon, 2014)

(untitled) - Hou, Z.; Wang, X.; Ikeda, T.; Terakura, K.; Oshima, M.; Kakimoto, M.-a.; Miyata, S. (Phys. Rev. B, 2012)

(untitled) - Lambin, P.; Amara, H.; Ducastelle, F.; Henrard, L. (Phys. Rev. B, 2012)

(untitled) - Lawlor, J. A.; Power, S. R.; Ferreira, M. S. (Phys. Rev. B, 2013)

(untitled) - Rani, P.; Jindal, V. K. (RSC Adv., 2012)

(untitled) - Nair, R. R.; Sepioni, M.; Tsai, I.-L.; Lehtinen, O.; Keinonen, J.; Krasheninnikov, A. V.; Thomson, T.; Geim, A. K.; Grigorieva, I. V. (Nat. Phys., 2012)

(untitled) - Singh, R.; Kroll, P. (J. Phys.: Condens. Matter, 2009)

(untitled) - Santos, E. J.; Sánchez-Portal, D.; Ayuela, A. (Phys. Rev. B, 2010)

(untitled) - Park, H.; Wadehra, A.; Wilkins, J. W.; Castro Neto, A. H. (Phys. Rev. B, 2013)

(untitled) - Rakyta, P.; Kormányos, A.; Cserti, J. (Phys. Rev. B, 2011)

(untitled) - Owens, J. R.; Cruz-Silva, E.; Meunier, V. (Nanotechnology, 2013)

(untitled) - Chen, T.; Li, X.-F.; Wang, L.-L.; Li, Q.; Luo, K.-W.; Zhang, X.-H.; Xu, L. (J. Appl. Phys., 2014)

Green’s functions in quantum physics - Economou, E. N. (Springer, 1984)

(untitled) - Lopez Sancho, M. P.; Lopez Sancho, J. M.; Rubio, J. (J. Phys. F: Met. Phys., 1984)

(untitled) - Kubo, R. (Can. J. Phys., 1956)

(untitled) - Power, S. R.; de Menezes, V. M.; Fagan, S. B.; Ferreira, M. S. (Phys. Rev. B, 2009)

(untitled) - Cheianov, V. V.; Syljuåsen, O.; Altshuler, B. L.; Fal’ko, V. I. (EPL, 2010)

(untitled) - Wan, W.; Li, H.; Huang, H.; Wong, S. L.; Lv, L.; Gao, Y.; Wee, A. T. S. (ACS Nano, 2013)

(untitled) - Khomyakov, P. A.; Giovannetti, G.; Rusu, P. C.; Brocks, G.; van den Brink, J.; Kelly, P. J. (Phys. Rev. B, 2009)

(untitled) - Xu, Z.; Buehler, M. J. (J. Phys.: Condens. Matter, 2010)

(untitled) - Wang, H.; Wang, Q.; Cheng, Y.; Li, K.; Yao, Y.; Zhang, Q.; Dong, C.; Wang, P.; Schwingenschlögl, U.; Yang, W.; Zhang, X. X. (Nano Lett., 2011)